PERAN LINGKUNGAN SOSIAL SEKOLAH DALAM PEMBENTUKAN KARAKTER KEAGAMAAN ISLAM PESERTA DIDIK KELAS VIII-A DI SMP NEGERI 2 ARSO KABUPATEN KEEROM - Siti Umi Kalsum; Zulihi; Annisa’ Fatmayanti (STKIP Subang, 2026)
This study aims to describe the role of the school social environment in shaping the Islamic religious character of Class VIII-A students at SMP Negeri 2 Arso, Keerom Regency; identify the inhibiting factors in the formation of students’ Islamic religious character; and describe the impact of the school social environment on students’ Islamic religious character. This research employed a qualitative method with a pedagogical approach. The primary data were obtained from the principal, teachers, and Class VIII-A students, while secondary data were obtained from learning documents, books, journals, school archives, and documentation. Data were collected through observation, in-depth interviews, and documentation, and analyzed through data reduction, data presentation, conclusion drawing, and verification. The findings show that the role of the school social environment in shaping students’ Islamic religious character consists of four main indicators: interaction among school members, school social climate, the role of teachers in the school social environment, and school culture and values. The inhibiting factors consist of three indicators: the influence of an unfavorable environment, weak social supervision at school, and an unsupportive family environment. Meanwhile, the impact of the school social environment is reflected in students’ faith and piety, noble character, and Islamic social behavior. Thus, the school social environment plays an important role in shaping the Islamic religious character of Class VIII-A students at SMP Negeri 2 Arso.